Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/soru.12317
|View full text |Cite
|
Sign up to set email alerts
|

Food that Matters: Boundary Work and the Case for Vegan Food Practices

Abstract: Meat and, less so, dairy are contested for their significant ethical and social‐ecological impacts. Abjuring animal products, veganism is conventionally treated as a dietary ideology related to consumer identities. Drawing upon practice and materialist turns, this article explores variations in the performance of veganism and how its boundaries are drawn. Yet, rather than an eating practice, I suggest to look at veganism more broadly and conceptualised as a food practice which also involves provisioning. By ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
(62 reference statements)
1
12
0
Order By: Relevance
“…There is a need for reconciliation by locating consumption within the wider context of political economy and elucidating practices within their systemic and material conditions for existence (Warde 2014 ; Evans 2020 ; see Welch et al 2020 for an overview). This resonates with recent empirical work combining practice and materialist turns to conceptualise veganism not only as a dietary identity but more broadly as a food practice that includes production (Hirth 2021 ). In acknowledgment of Evans, who calls for “new conceptual vocabulary” ( 2020 , p. 4) to think across the production-consumption dualism, this study combines consumers’ everyday food practices with food sustainability discourses and, by emphasising the imperial character of food provision, elucidates both against the background of the wider political economy.…”
Section: Locating (Ethical) Consumption Within the Wider Political Economysupporting
confidence: 58%
See 1 more Smart Citation
“…There is a need for reconciliation by locating consumption within the wider context of political economy and elucidating practices within their systemic and material conditions for existence (Warde 2014 ; Evans 2020 ; see Welch et al 2020 for an overview). This resonates with recent empirical work combining practice and materialist turns to conceptualise veganism not only as a dietary identity but more broadly as a food practice that includes production (Hirth 2021 ). In acknowledgment of Evans, who calls for “new conceptual vocabulary” ( 2020 , p. 4) to think across the production-consumption dualism, this study combines consumers’ everyday food practices with food sustainability discourses and, by emphasising the imperial character of food provision, elucidates both against the background of the wider political economy.…”
Section: Locating (Ethical) Consumption Within the Wider Political Economysupporting
confidence: 58%
“…Traditionally relying heavily on beef (which, compared to other meats, has the highest environmental footprint; de Ruiter et al 2017 ), McDonald’s has reacted to the popularisation of ‘plant-based’ diets by expanding its product range by adding meatless options. Whilst in its sustainability report McDonald’s does address meat’s problematic feed efficiency ratio, on the one hand, and the fact that more people become vegan, vegetarian, or flexitarian, on the other, it does not connect these topics semantically, treating the latter one as a mere question of lifestyle and identity without putting it in the context of (ecological) sustainability (see also Hirth 2021 ). This resonates with Ehgartner’s observation “that rather than the problem of meat consumption being discussed, it is the opportunity of protein diversity , which is mobilised” ( 2020 , p. 480).…”
Section: Systematic Change: Discursive Frames Of Food Sustainabilitymentioning
confidence: 99%
“…Clear communication between farmers, retailers, consumers, and other actors will be an important component of market expansion. For instance, as illustrated by the UK media inaccurately describing what “vegan organic” means and why farmers grow this way (Hirth 2020 ), accurate messaging will be critical for cultivating public understanding and acceptance of veganic agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…One case study of a veganic farm in the United States indicates that the owner-operators chose to practice veganic agriculture to align their organic-certified operation with their recent personal transition to veganism (Seymour forthcoming). Another case study of a vegan organic farm in the United Kingdom suggests that the former cattle farmers transitioned to veganic agriculture out of care and concern for animal welfare, food security, and the environmental and climate impacts of cattle production (Hirth 2020 ). Schmutz and Foresi reported on a small German-language study of vegan organic growers’ motivations for excluding animal inputs, which found ethical, social, and ecological motives for this practice, suggesting that it is an “idealistic” approach ( 2017 , p. 476).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation